AUDITORS' PROFESSIONAL SKEPTISM AND ABILITY TO DETECT FRAUD IN PUBLIC ACCOUNTING FIRM IN MEDAN CITY - Sijabat, Jadongan; Munte, Mei Hotma M.; Anugerah, Billy (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2024)
This research is an empirical study regarding professional skepticism and the ability to detect fraud. This research aims to examine the influence of professional skepticism on the ability to detect fraud.This research was conducted using a survey method at the Public Accounting Firm in the city of Medan. The unit of analysis is the auditors. Simple linear regression analysis with the help of SPSS Statistics 20 was used to analyze the data.The findings of this research indicate that professional skepticism has a significant positive effect on the ability to detect fraud. This finding explains that the higher the professional skepticism of auditor the higher the auditor's ability to find fraud so that the possibility of fraud will be smaller.